Role of E-Learning in Teaching Anatomical Sciences - Amin Zand; Hojjat Allah Abbaszadeh; Mohammad Amin Abdolahifar; Abbas Ali Aghaee; Abdollah Amini; Reza Mastery Farahni (Negah Institute for Scientific Communication, 2016)
Introduction: Medical undergraduates usually understand and memorize anatomical course material with difficulty. Also, the current text books and atlases of anatomy and histology do not fulfill all the learning needs of the undergraduates. Therefore, it is necessary to consider the role of internet websites and computer programs (i.e. the role of electronic learning) in teaching. The present research aimed to introduce the new teaching facilities in the field of anatomical sciences to improve learning among medical undergraduates and ameliorate the present teaching deficiencies. The present research also aimed at facilitating the continual training of graduates and lecturers in the anatomical sciences. Methods: In this research, content analysis was conducted on 9 internet websites and 4 projects and computer programs related to anatomical sciences on the basis of those introduced by the lecturers of the anatomical sciences department of medicine faculty of Shahid Beheshti University of Medical Sciences. This review was conducted on the basis of teaching processes and technologies needed in electronic learning environment and also the necessary teaching facilities in learning of the anatomical sciences. Results: Having interactive programs, atlases and virtual tests, the capability of updating material and continual education are some of the properties of electronic learning environments in the teaching of anatomical sciences. According to this research, 100% of the investigated projects and the computer programs and 44% of the websites, had interactive programs. Furthermore, 50% of the projects and computer programs and 22% of websites had virtual updated atlases, and 22% of websites had virtual tests. Conclusion: By using the facilities in reliable educational sites of anatomical sciences and also the interactive learning computer programs, difficulties in learning and understanding anatomical sciences syllabus can be reduced and the level of knowledge in the field raised so that the way can be paved for improving clinical skills in the areas of diagnosis and treatment. Besides, the use of these technologies is effective in updating the knowledge of graduates and lecturers in the field of anatomical sciences.